Frailty and emergency abdominal surgery: A systematic review and meta-analysis. Issue 6 (December 2022) - Kennedy, Czara Annamaria; Shipway, David; Barry, Kevin
Abstract: Introduction: Patients aged ≥65 years currently account for approximately 55% of all emergent operations. However, these patients account for 75% of post-operative mortality. Older age has long been associated with adverse outcomes from emergency surgery. However, old age is a heterogenous state. Recent studies have indicated that frailty may more accurately reflect true biological age and perioperative risk than chronological age alone in patients undergoing elective surgery. Few studies have evaluated the impact of frailty on post-operative outcomes in this setting. Methods: A systematic, electronic search for relevant publications was performed in November 2019 using Pubmed and Embase from 2009 to 2019. The latest search for articles was performed on February 16th, 2020. Articles were excluded if frailty was not measured using a frailty tool, or if patients did not undergo emergency general surgery (EGS). Results: The prevalence of frailty amongst patients undergoing emergency abdominal surgery was 30.8%. The all-cause mortality rate was 15.68%. The mortality rate amongst the frail undergoing EGS was 24.7%. Frailty was associated with an increased mortality rate compared with the non-frail (odds ratio (OR) 4.3, 95% CI 2.25–8.19%, p < 0.05, I 2 = 80%). Conclusions: There is strong evidence to suggest that frailty in the older population predicts post-operative mortality, complications, prolonged length of stay and the loss of independence. Collaborative working with medicine for the elderly physicians to target modifiable aspects of the frailty syndrome in the perioperative pathway may improve outcomes. Frailty scoring should be integrated into acute surgical assessment practice to aid decision-making and development of novel postoperative strategies. Highlights: Populations are ageing, as are the number of patients who require emergency surgery The prevalence of frailty amongst patients undergoing emergency surgery was 29.2% The mortality rate amongst the frail undergoing emergency general surgery was 24.7% These findings support the integration of a frailty pathway to improve outcomes